Plant Growth and Soil Microbial Impacts of Enhancing Licorice With Inoculating Dark Septate Endophytes Under Drought Stress - He, Chao; Wang, Wenquan; Hou, Junling (Frontiers in Microbiology, 2019)
This study mainly aimed to investigate the effects of dark septate endophytes (DSE) (Acrocalymma vagum, Paraboeremia putaminum and Fusarium acuminatum) on the growth and microbial community composition in the rhizosphere soil of a medicinal plant, liquorice (Glycyrrhiza uralensis), grown in the non-sterile soil under drought stress. The results showed that three DSE strains could effectively colonize the plant roots and formed a strain-dependent symbiosis with liquorice. Although drought stress declined the growth of liquorice plants, these decreases were partly recovered by DSE inoculation. Specifically, the inoculation of A.vagum and P. putaminum significantly increased the biomass and glycyrrhizin content, whereas A. vagum and F. acuminatum increased glycyrrhizic acid content of host plants under drought stress. However, the inoculation of F. acuminatum showed significantly and negatively effects on the shoot, root and total biomass of liquorice plants. In addition, the effects of DSE inoculation on the morphological, photosynthetic and antioxidant parameters of liquorice plants, and mineral nutrient and microbial community composition in the rhizosphere soil were dependent on the DSE species as well as water regime. Interestingly, DSE inoculation significantly increased AM fungi content under drought stress. In addition, DSE associated with water significantly positively influenced soil organic matter, available phosphorus (P), AM fungi, leaf number, soluble protein, SOD activity, total root length, root branch and glycyrrhizic acid content. Based on the results of variance partitioning analysis, 17.0 %, 34.0 %, 14.9 %, 40.1 %, 28.2 % and 18.0 % variations in shoot morphology, root morphology, plant biomass, active ingredient, photosynthetic parameters, and antioxidant parameters respectively, were attributable to the presence of certain soil microorganisms. These findings suggest the possibility that DSE inoculation improved the root development and nutrient absorption of host plants and altered the soil microbiota, might contribute to plant growth and survival under drought conditions. As A.vagum exhibited positive effects on the plant biomass, morphological and physiological parameters, and active ingredient content in liquorice plants under drought stress, it was considered to be the best fungus for the liquorice cultivation. These results contribute to the understanding of the ecological function of DSE fungi in dryland agriculture.